(untitled) (International Journal of Engineering and Computer Science, 2017)
A wireless sensor network (WSN) as the name suggest is a wireless network with spatially distributed autonomous devices making use of sensors for monitoring physical or environmental conditions. WSNs find applications in areas like healthcare, home automation, traffic control etc. WSN with characteristics of self-organization, multi-hop, dynamic topology and limited energy resources, make it extremely difficult to prolong the lifetime of the network. To prolong the life time of WSN with limited energy resources, Multicast can better meet the requirements of network resources. It has an active significance for WSN to increase its performance in the near future. In Wireless sensor networks sensor nodes are grouped together by forming multicast groups. The communication among the nodes is done by broadcasting and multicasting efficient message deliveries among resource-constrained sensor nodes. Two group key protocols are developed for secure multicast communications among the resource-constrained devices. The proposed approach compares the performance of two protocols with ten nodes in each group. We analyze the proposed solution to evaluate the performance using Network Simulator-2 (NS-2) under different network parameters with a number of destination nodes.